Growth problems in wealthy LDCs - Klaus E. Rohde (Intereconomics, 1972)
Large revenues drawn from oil offer wide scope for a highly active development policy, especially to the oil producing states round the Arab-Persian Gulf (which is to be understood as a geographical, not a political term). But even countries In such a favoured situation experience bottlenecks, and also the direction In which their economic and social structures of the future may move is full of pitfalls.
Keywords: 330; Developing countries